State and Criminal Law of the East Central European Dictatorships - Kozerska, Ewa; Scheffler, Tomasz (Lectures on East Central European Legal History, 2022)
The chapter is devoted to discussing constitutional and criminal law as it existed in selected countries of Central and Eastern Europe between 1944 and 1989 (Czechoslovakia, the German Democratic Republic, Romania, Hungary, and Poland). As a result of the great powers’ decisions, these countries came under the direct supervision of the Soviet Union and adopted totalitarian political solutions from it. This meant rejecting the idea of the tripartite division of power and affirming the primacy of the community (propaganda-wise: the state pursuing the interests of the working class) over the individual. As a result, regardless of whether the state was formally unitary or federal, power was shaped hierarchically, with full power belonging to the legislative body and the body appointing other organs of the state. However, the text constantly draws attention to the radical discrepancy between the content of the normative acts and the systemic practice in the states mentioned. In reality, real power was in the hands of the communist party leaders controlling society through an extensive administrative apparatus linked to the communist party structure, an apparatus of violence (police, army, prosecution, courts, prisons, and concentration and labor camps), a media monopoly, and direct management of the centrally controlled economy. From a doctrinal point of view, the abovementioned states were totalitarian regardless of the degree of use of violence during the period in question. Criminal law was an important tool for communist regimes’ implementation of the power monopoly. In the Stalinist period, there was a tendency in criminal law to move away from the classical school’s achievements. This was expressed, among other means, by emphasizing the importance of the concept of social danger and the marginalization of the idea of guilt for the construction of the concept of crime. After 1956, the classical achievements of the criminal law doctrine were gradually restored in individual countries, however – especially in special sections of the criminal codes – much emphasis was placed on penalizing acts that the communist regime a priori considered to be a threat to its existence. Thus, also in the field of criminal law, a difference was evident between the guarantees formally existing in the legislation and the criminal reality of the functioning of the state. KEYWORDS: state law, criminal law, communist regime, East Central Europe.